AB0816 QUALITY OF LIFE AND TREATMENT SATISFACTION IN CHINESE PATIENTS WITH CHRONIC KNEE OSTEOARTHRITIS PAIN: A CROSS-SECTIONAL STUDY. (June 2019) - Xue, Qingyun; Long, Huibin; Lin, Jianhao; Du, Dongping; Zhou, Jin; Chen, Jinwei; Shu, LI; Zhang, Yanlei; Cheng, Yan; Xiao, MA; Zhang, Zhiyi
Abstract : Background: Joint pain is one of the most common symptoms of osteoarthritis (OA) and affects the physical function and quality of life of patients. Objectives: To understand the impact of chronic pain due to knee OA on health-related quality of life (HRQoL) and evaluate treatment satisfaction of current medications among Chinese patients. Methods: A cross-sectional survey was conducted in orthopedics, rheumatology and pain departments in five first-class hospitals in China from March to October 2018. Eligible patients were ≥40 years old, with diagnosed knee OA, experiencing joint pain for at least 3 months and receiving oral medications during the past 12 months. Socio-demographics, disease characteristics, Brief Pain Inventory (BPI), treatment information, Treatment Satisfaction Questionnaire for Medication (TSQM-1.4), and HRQoL (EQ-5D-5L) were assessed. Descriptive analysis and t-test were used for statistical analysis. Results: A total of 601 patients were included and 75.2% of them were female. The mean (SD) age was 61.77 (9.53) years. More than half (55.1%) had at least 1 comorbidity. The most common comorbidities were hypertension (39.8%), diabetes (15.3%), gastritis (14.3%) and coronary heart disease (12.5%). The mean (SD) age at first diagnosis of knee OA was 58.13 (9.62) years. The most commonly used current treatments for knee OA were oral medication (78.0%), followed by patch or ointment (45.1%) and intra-artlar hyaluronic acid injection (31.5%). The mean (SD) of BPI-Severity and BPI-Interference ratings were 3.78 (1.62) and 2.97 (1.70), respectively. More than half (52.9%) of patients rated BPI-average pain ≥4. Around 37.1% of patients reported ≥4 days per week of work or housework loss due to OA pain. Overall, the mean (SD) score of EQ-5D-5L is 0.72 (0.21). Patients with BPI-average pain ≥4 reported significantly lower EQ-5D-5L score than those with BPI-average pain <4 (0.62 vs 0.84, p<0.0001). The mean (SD) scores of TSQM effectiveness, side effects, convenience and global satisfaction were 54.19 (14.13), 96.00 (10.93), 62.30 (10.42) and 58.97 (15.43), respectively. The scores in all of the four dimensions of TSQM were lower in patients with BPI-average pain ≥4 than in those with BPI-average pain <4 (effectiveness: 51.01 vs 57.81, p<0.0001; side effects: 94.91 vs 97.24, p=0.0099; convenience: 60.18 vs 64.71, p<0.0001; global satisfaction: 57.74 vs 60.35, p=0.0402). Conclusion: Chronic pain due to knee OA, especially moderate to severe pain, has significant impact on patients' HRQoL and work productivity. Patients were not satisfied with current treatments. There are unmet needs for better pain management including more drug choices in China to improve the treatment satisfaction. Acknowledgement: Qingyun Xue and Huibin Long equally contributed to the study. Zhiyi Zhang is the corresponding author. Disclosure of Interests: Qingyun Xue: None declared, Huibin Long: None declared, Jianhao Lin: None declared, Dongping Du: None declared, Jin Zhou: None declared, Jinwei Chen: None declared, Shu Li: None declared, Yanlei Zhang Employee of: Eli Lilly Employee, Yan Cheng Employee of: Eli Lilly Employee, Xiao Ma Employee of: Eli lilly Employee, Zhiyi Zhang: None declared